The Paris Agreement: Short-Term and Long-Term Effectiveness - Guri Bang; Jon Hovi; Tora Skodvin (Politics and Governance, 2016)
The 2015 Paris Agreement was widely greeted with enthusiasm. We assess the short-term and long-term potential effectiveness of Paris. Concerning short-term effectiveness, we contend that while Paris scores high on participation, and reasonably high on the depth of the parties’ commitments (ambition), its Achilles’ heel will likely be compliance. Concerning long-term effectiveness, we argue that Paris does little to restructure states’ incentives so as to avoid free riding. At worst, it might end up as a failure, much like Kyoto did. On the other hand, domestic and international norms could continue to develop in a direction that makes it more and more difficult for individuals, firms, and states alike to ignore the plea to limit and reduce their carbon footprints. Technological progress that gradually reduces abatement costs, combined with leadership by major emitters such as the United States, might further strengthen climate cooperation and enhance other countries’ willingness to follow through. However, deep political polarization continues to represent a significant barrier to U.S. leadership on climate change.